Structural and crystal-chemical characteristics of the apatite deposits from human aortic walls - Danilchenko, Sergei N.; Kalinkevich, Aleksei N.; Moskalenko, Roman A.; Kuznetsov, Vladimir N.; Kochenko, Aleksandr V.; Husak, Evgenia V.; Starikov, Vadim V.; Liu, Fuyan; Meng, Junhu; Lu, Jinjun (Akadémiai Kiadó, 2018)
Thermal behavior of biological apatite is the object of several studies. Crystal size, carbonate content, phase composition, and other parameters change during annealing up to 900 °C in biological minerals with apatite structure. The way these parameters change reflects the specific properties of the initial bioapatite. This work presents data on thermal transformations of pathological bioapatite from the human cardiovascular system, namely aortic wall deposits. Some minor elements, foreign to calcium hydroxyapatite (e.g., Na and Mg), can be both incorporated in the apatite structure and localized in the surface layers of crystals, modifying functions of the mineral. A new approach was proposed to determine the predominant location of minor elements, such as Mg, Na, and K, in the mineral of pathological deposits. Mg and Na in pathological apatite can be in both structurally bound (substituting calcium in lattice) and labile (localized on the crystal surface) states, while K is not able to join the apatite structure in significant amount or be chemically bound to it. This approach, based on atomic spectrometry, can be used effectively in combination with a set of traditional techniques, such as like EDS, IRS, and XRD.
Keywords: biomineralization; pathological mineralization; crystallization; electron microscopy; X-ray crystallography